MOCK Q&A WITH CAMMER AND FORSCEY FOR APRIL 10 HEARING (Tufts Archival Research Center, 2007)
Transcript of mock question and answer session with Cammer and Forscey to prepare for an April 10. 1991 hearing regarding the Business Council for Indoor Air (BCIA). Denies affiliations with the tobacco industry or knowledge of the health effects of secondhand smoke. Discusses implementation of a regulatory program and what agency should administer this program.